First Report of Genus Plumeria L. (1753) in Ternate Island as The Flora Ternate Database - Suparman Suparman; Abdulrasyid Tolangara; Hasnah Ahmad; Wa Ode Risnawaty; Magfirah Rasyid (Universitas Khairun, 2023)
The genus Plumeria Tourn ex. Linn., family Apocynaceae Juss officially has 20 accepted species from around the world. The genus is native from Mexico to Caribbean; however, it was introduced to some part of world especially to tropical area. In this paper, we formally reported for the first time the data for the genus Plumeria in Ternate, North Maluku, Indonesia. The exploration research was conducted from March to June 2022 for around Ternate Island. All species of Plumeria spp are noted and collected from 21 villages as representative of five subdistricts in Ternate Island. Three accepted species namely Plumeria obtusa L., P. pudica Jacq., dan P. rubra L are validated in Ternate. All species are discovered as ornamental plant and cemetery marker. P. obtusa is the most common species found in many villages followed by P. rubra. This publication shares information about location, general utility, and key identification for every species